PENGARUH MODEL PEMBELAJARAN GIPS (GUIDED INQUIRY PROBLEM SOLVING) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA MATERI HIDROLISIS GARAM - Aroma Kusuma Dewi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstrak. Research on the effect of learning model GIPS (Guided Inquiry Problem Solving) on the material salt hydrolysis. This study aims to determine: (1) differences in students critical thinking ability (2) differences in student learning achievement (cognitive, affective, psychomotor) on the material salt hydrolysis on a learning model GIPS (Guided Inquiry Problem Solving) and model GI (Guided Inquiry), (3) The students' response to the learning model GIPS on the material salt hydrolysis. This study uses nonequivalent pretest-posttest control group design. The research sample as many as 72 students, the class XI MIA 2 and 3. Samples were taken using cluster random sampling. The data collection technique using the test critical thinking ability and cognitive learning, observation and questionnaires. Data were analyzed using descriptive analysis (N- gain) and inferential analysis (normality test, homogeneity test, and t-test). The results of this study indicate that (1) there is a difference significant critical thinking ablity (2) there are differences significant in student learning achievement (cognitive, affective, psychomotor) between students who use GIPS learning model with students using GI learning model. (3) students responded positively to the learning model GIPS on material salt hydrolysis.Keywords: model GIPS (guided inquiry problem solving), critical thinking skills, learning outcomes (cognitive, affective, psychomotor), response, salt hydrolysis